ONBOARD COMPUTER COMPLEX USING THE SERVICE OF VERBAL INTERACTION - Vasilij M. Trembach (Открытое образование (Москва))
The article examines the approaches and methods of use onboard computing systems for various purposes, using the services of speech interaction. The mechanisms and methods of constructing and voice interfaces. It shows a demo unit of verbal interaction.